Sistem Informasi Geografis Berbasis Layanan Publik Pada Ombudsman Provinsi Gorontalo - Mohamad Rezkarnin Yahya; Salahudin Olii; Roviana H. Dai; Tajuddin Abdillah (Diffusion: Journal of Systems and Information Technology, 2023)
Public services are a series of activities in fulfilling service needs in accordance with the provisions on goods, services and administration provided by service providers. certain public services in which part or all of the funds come from the state revenue and expenditure budget and/or the regional revenue and expenditure budget. This research was conducted as a means of receiving and verifying the location of the complainant to the ombudsman in Gorontalo Province. The method used in this study is the prototype method and system design using UML design, which consists of (use case diagrams, activity diagrams, sequence diagrams, and class diagrams). The final result of this research is to produce a geographic information system for public services to the Indonesian ombudsman for Gorontalo representatives, which can assist in disseminating information related to reporting to the ombudsman and assistant ombudsman can verify reports and report locations from the public